Model and Simulation of a Tunable Birefringent Fiber Using Capillaries Filled with Liquid Ethanol for Magnetic Quasiphase Matching In-Fiber Isolator. (4th May 2010) - Zeringue, Clint; Moore, Gerald T.
Abstract : A technique to tune a magnetic quasi-phase matching in-fiber isolator through the application of stress induced by two mutually orthogonal capillary tubes filled with liquid ethanol is investigated numerically. The results show that it is possible to "tune" the birefringence in these fibers over a limited range depending on the temperature at which the ethanol is loaded into the capillaries. Over this tuning range, the thermal sensitivity of the birefringence is an order-of-magnitude lower than conventional fibers, making this technique well suited for magnetic quasi-phase matching.